Postoperative testicular metastasis in early to mid-stage gastric adenocarcinoma: a case report and literature review - Huang, Yuanshun; Xu, Mengshuang; Zhang, Yaoyu; Xue, Yuan; Wang, Lijun; Huang, He; Li, Wei; Li, Shadan (Frontiers in Oncology, 2025)
This study reports a case of a 59-year-old male who primarily presented with a testicular mass accompanied by pain, ultimately diagnosed as testicular metastasis from gastric adenocarcinoma. Over three years earlier, the patient underwent radical gastrectomy for gastric adenocarcinoma, followed by eight cycles of S-1 and oxaliplatin chemotherapy. On February 10, 2025, the patient presented to our hospital with a history of a left testicular mass that had persisted for over a year. He experienced recurrent, palpable pain in the right scrotal and inguinal regions. Contrast-enhanced computed tomography (CT) revealed a cystic and solid mass in the left testis; it displayed heterogeneous density, with punctate and linear enhancement within the parenchyma on contrast scans, showing a “fast in, fast out” pattern, while no significant enhancement was observed within the cystic lesion. Consequently, a left radical orchiectomy was performed, and histopathology confirmed metastatic gastric adenocarcinoma. This case provides new data for the clinical recognition of rare metastatic patterns of gastric cancer, highlighting the necessity of considering and investigating its clinical features, potential pathogenesis, and effective strategies to further prevent metastasis.